Trachelogenin alleviates osteoarthritis by inhibiting osteoclastogenesis and enhancing chondrocyte survival - Tao Jiang; Jiahui Zhang; Beite Ruan; Xiaobing Xi; Zhuo Yang; Jianmin Liu; Hongyan Zhao; Xing Xu; Min Jiang (BMC, 2024)
Abstract Background Osteoarthritis (OA) is a prevalent global health concern associated with the loss of articular cartilage and subchondral bone. The lack of disease-modifying drugs for OA necessitates the exploration of novel therapeutic options. Our previous study has demonstrated that traditional Chinese medical herb Trachelospermum jasminoides (Lindl.) Lem. extract suppressed osteoclastogenesis and identified trachelogenin (TCG) as a representative compound. Here, we delved into TCG's potential to alleviate OA. Methods We initially validated the in vivo efficacy of TCG in alleviating OA using a rat OA model. Subsequently, we isolated primary bone marrow-derived macrophages in vitro to investigate TCG's impact on osteoclastogenesis. We further employed a small molecule pull-down assay to verify TCG's binding target within osteoclasts. Finally, we isolated primary mouse chondrocytes in vitro to study TCG's regulatory effects and mechanisms on chondrocyte survival. Results TCG preserved subchondral bone integrity and protected articular cartilage in a rat OA model. Subsequently, in vitro experiments unveiled TCG's capability to inhibit osteoclastogenesis and function through binding to Ras association proximate 1 (Rap1) and inhibiting its activation. Further study demonstrated that TCG inhibited Rap1/integrin αvβ3/c-Src/Pyk2 signaling cascade, and consequently led to failed F-actin ring formation. Besides, TCG promoted the proliferation of mouse primary chondrocytes while suppressing apoptosis in vitro. This is attributed to TCG's ability to upregulate HIF1α, thereby promoting glycolysis. Conclusion TCG exerted inhibitory effects on osteoclastogenesis through binding to Rap1 and inhibiting Rap1 activation, consequently preventing subchondral bone loss. Moreover, TCG enhanced chondrocyte survival by upregulating HIF1α and promoting glycolysis. These dual mechanisms collectively provide a novel approach to prevented against cartilage degradation.